2022
DOI: 10.1101/2022.02.03.479037
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mRNA-1273 or mRNA-Omicron boost in vaccinated macaques elicits comparable B cell expansion, neutralizing antibodies and protection against Omicron

Abstract: SARS-CoV-2 Omicron is highly transmissible and has substantial resistance to antibody neutralization following immunization with ancestral spike-matched vaccines. It is unclear whether boosting with Omicron-specific vaccines would enhance immunity and protection. Here, nonhuman primates that received mRNA-1273 at weeks 0 and 4 were boosted at week 41 with mRNA-1273 or mRNA-Omicron. Neutralizing antibody titers against D614G were 4760 and 270 reciprocal ID50 at week 6 (peak) and week 41 (pre-boost), respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
66
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 91 publications
(123 reference statements)
9
66
3
Order By: Relevance
“…However, our data argued that the heterologous booster scheme is not superior to boosting with the ancestral WA mRNA in terms of establishing immunity against Omicron ( Figure 5E ). Similar conclusion was drawn by a research group from NIH, when they challenged mRNA-1273-vaccinated macaques with live omicron virus 31 . A plausible explanation is although Omicron S protein has ~35 mutations, it still exhibits 97% similarity to the ancestral WA strain in the amino acid sequence.…”
Section: Discussionsupporting
confidence: 77%
“…However, our data argued that the heterologous booster scheme is not superior to boosting with the ancestral WA mRNA in terms of establishing immunity against Omicron ( Figure 5E ). Similar conclusion was drawn by a research group from NIH, when they challenged mRNA-1273-vaccinated macaques with live omicron virus 31 . A plausible explanation is although Omicron S protein has ~35 mutations, it still exhibits 97% similarity to the ancestral WA strain in the amino acid sequence.…”
Section: Discussionsupporting
confidence: 77%
“…However, Omicron-mRNA boost in vaccinated macaques has not displayed significantly different NAb titers and B cells response 24 . This could be due to different immunization intervals and antigen epitopes.…”
Section: Discussionmentioning
confidence: 88%
“…As a booster with Omicron-matched DNA vaccines, increased width of immune response has been observed 23 . However, in macaque models, vaccination with Omicron-specific boosters do not increase neutralizing antibody (NAb) titers against Omicron and remain the equivalent levels of B cell response 24 . Of note, both two types of vaccines were designed according to full-length spike proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Critically, our results provided explicit evidence that Omicron can drastically attenuate its antigenicity across all epitopes on the RBD, which is the key target by neutralizing antibodies. During our manuscript preparation, a preprint reported that an Omicron-specific mRNA vaccine boost appears to provide inferior protection against Omicron infection in non-human primates compared to boost using the WT mRNA vaccine 20 . Moreover, new clinical data suggested that the antibody titers after Omicron breakthrough cases were lower than those of after Delta infection [2][3][4][5][6][7][8] .…”
Section: Discussionmentioning
confidence: 99%